Coconut based cropping systems for enhancing profitability, ensuring sustainability and transcending towards nutritional security - Karun, Anitha; Jayasekhar, S; Muralidharan, K (Indian Horticulture, 2022)
Coconut is considered as one of the most important crops for the Asia and Pacific region, providing food, nutrition and livelihood to millions of coconut farmers in the region. Despite the economic importance of the coconut palm, coconut production continued to show stagnancy in production, productivity and trade in the recent decade. The coconut sector in the past has been dominated by copra and coconut oil, and the international coconut trade used to be driven by the demand for coconut oil. However, demand for coconut oil has witnessed a sharp decline during the last decades due to increased competition from other edible oils, such as palm oil and soybean. Furthermore, there is a changing trend wherein coconut is increasingly being processed into diversified value-added products in recent times. This emerging trend has influenced the current production, processing and trading system in coconut. To take advantage of these newfound opportunities in the world market, coconut growers must look into the trade patterns, performance and global competitiveness of coconut and coconut products. At present, the market trends indicate consumer choice and acceptance of the various products of coconut. Growth rates in export volumes continue to increase each year for Virgin Coconut Oil (VCO) by 30%, Coconut Water by 150%, Coconut Milk/Cream/ Powder by 50%, Desiccated Coconut by 30%, Coconut Flour by 115% and similar trends for other emerging products. Taking a cue from the changed scenario in the coconut sector, the Kalpa Agri-Business Incubator functioning under ICAR-CPCRI provides muchneeded handholding to the startup entrepreneurs in the sector.